2017
DOI: 10.20473/jn.v12i2.6026
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Characteristics of Colostomy Patients

Abstract: Introduction: Colostomy imposed multiple impacts on the patient's life including physical, psychological, social, and spiritual. This study aims to identify the level of quality of life as well as to examine the differences of quality of life among colostomy patients with regards to certain demographic characteristics. Methods: This study used a cross-sectional and descriptive analytical approach. Seventy-one colostomy patients were recruited purposively to participate in the study. The studied variables inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Decision making is the same as adopting an innovation, which is the process of starting and releasing ideas from someone, then conveying them to a second party, until the idea is accepted by the second party. 12 The majority of PLWHA decision making regarding chatbot innovation was 77.7% (28 people) choosing to accept this chatbot innovation. It was found that only (22.2%) as many as 8 people chose to reject the chatbot innovation that was introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Decision making is the same as adopting an innovation, which is the process of starting and releasing ideas from someone, then conveying them to a second party, until the idea is accepted by the second party. 12 The majority of PLWHA decision making regarding chatbot innovation was 77.7% (28 people) choosing to accept this chatbot innovation. It was found that only (22.2%) as many as 8 people chose to reject the chatbot innovation that was introduced.…”
Section: Discussionmentioning
confidence: 99%